Women in Contemporary Islamic Perspective: Between Equality and Nature - Mohammed Abdu Rehany (Aafiyah: Jurnal Multidisiplin Ilmu, 2024)
The discourse concerning women in contemporary Islamic perspectives continues to develop alongside social transformation, globalization, educational progress, and debates regarding gender equality and women’s rights. Islam recognizes the dignity, honor, and important social roles of women while also acknowledging natural differences between men and women in certain biological and social dimensions. However, interpretations regarding equality and women’s nature often generate debate within contemporary Muslim societies, particularly concerning education, leadership, employment, family roles, and public participation. This study aims to analyze women’s positions in contemporary Islamic perspectives by examining the relationship between gender equality and women’s natural characteristics within social and religious contexts. The research employs a qualitative descriptive approach through literature review and contextual analysis of Islamic teachings, gender discourse, and contemporary social realities. The findings indicate that Islam fundamentally upholds human dignity, justice, educational rights, social participation, and ethical equality between men and women while recognizing complementary roles and biological distinctions between genders. The study also reveals that contemporary challenges such as patriarchal culture, gender discrimination, globalization, and modern feminist discourse influence interpretations regarding women’s roles in Muslim societies. Therefore, balanced understanding integrating Islamic values, social justice, and recognition of women’s nature is essential for promoting women’s empowerment and harmonious social development in contemporary society.